Analysis of Workload and Job Satisfaction of Rocket Chicken Employees at the Ampana City Branch - Siti Aisa A Fau; Lindanur Sipatu; Rosida Adam; Arie Kurniawan (Journal of Educational Management Research, 2025)
This study analyzes factors influencing employee job satisfaction at Rocket Chicken Ampana Branch, focusing on workload, sales targets, working conditions, Time management, work standards, promotion opportunities, and supervision. The research design used a qualitative case study approach, with data collected through interviews, observations, documentation, and audiovisual recordings from seven informants. The results show that, despite challenges such as high workloads and customer complaints, employees feel satisfied thanks to a clear system, supervisor support, and opportunities for career growth. Motivational factors such as incentives, fair compensation, and promotion opportunities play an important role in balancing job demands and personal satisfaction. The study also found that work experience and flexible Time management increase employee job satisfaction. The practical implications of this research are the importance of creating a work environment that supports employee wellbeing and provides equal career development opportunities for all employees.